Coeval calc-alkaline and alkaline Cadomian magmatism in the Bafq, central Iran: Insights into their petrogenesis - Sepidbar, F; Ghorbani, G; Zoheir, B; Palin, R; Homam, SM; Zafar, T; Ma, J; He, L (Elsevier, 2021)
The Chah-Gaz and Mishdovan areas in the Bafq magmatic complex, central Iran, contain thick series of terrigenous sediments (the Rizu-Dezu complex), and arc-related calc-alkaline and alkaline igneous rocks. Geochemical analyses of igneous rocks from both areas indicate two distinct rock clans: (1) high-K, calc-alkaline-shoshonitic rocks with strong depletions in Nb, P, and Ti, and (2) an alkaline quartz gabbro-diorite, with trace element patterns resembling oceanic island basalts (OIB). New geochronological data reveal that magmatic rocks of both clans crystallized almost simultaneously, with zircon U[sbnd]Pb ages of 534 Ma and 537 Ma, respectively. The whole-rock Nd[sbnd]Sr isotopic data ((87Sr/86Sr)(I) = 0.7052 to 0.7064 and ɛNd(t) = +1.3 to +2.7) of alkaline quartz gabbro-diorite indicate an enriched OIB-like mantle source, while the high-K, calc-alkaline-shoshonitic rocks have εNd(t) = −5.5 to −7.6, clearly reflecting significant contributions from pre-existing Proterozoic basement. Apatite in both the Chah-Gaz and Mishdovan magmatic rocks is of magmatic origin, with light rare earth element (LREE) enrichment patterns. The low Sr/Y and Eu/Eu⁎ values in apatite demonstrate the non-adakitic character of the investigated rocks, while the moderately negative Eu anomaly and inverse correlation between δCe and δEu in the analyzed apatites may reflect reduced parental magmas. The geochemical and isotopic results presented here indicate that slab rollback and opening of an extensional basin could have initiated concurrent Cadomian arc-related calc-alkaline and rift-associated alkaline magmatism in the Chah-Gaz and Mishdovan areas.